SRIKANDI AND INDONESIA’S E-GOVERNMENT POLICY: SYSTEM RELIABILITY AND THE CRUCIAL ROLE OF POLITICAL COMMITMENT - Zakaria, Tubagus Zaki; Deliarnoor, Nandang Alamsah; Sukarno, Dedi (Universitas Padjadjaran, 2025)
This study examines the implementation of the SRIKANDI e-government policy in Indonesia, focusing on six critical elements: information exchange, information security, citizen engagement, human resources, inter-agency services, and policy-related decision-making. Employing a qualitative research methodology, NVIVO software was used to conduct thorough data coding and content analysis. Data were collected through literature reviews, non-participant observations, in-depth interviews, and analysis of official government documents, ensuring robust triangulation and comprehensive understanding. The findings reveal significant challenges in information security, particularly with system vulnerabilities that pose risks to data integrity. The level of citizen engagement remains low, with existing regulations limiting public participation in the development and use of the G2G system. Human resource issues, especially in regional areas, highlight gaps in both technical skills and staffing adequacy. System reliability, a crucial discovery, emphasizes the need for stable microservices architecture and proper integration of blockchain technology development to ensure seamless operation. Moreover, political commitment emerges as the primary driver in policy-related decision-making, with clear discrepancies between regional leadership affecting implementation success. The study finds that stronger political will and alignment between government levels are necessary for realising SRIKANDI’s full potential. This research contributes to a deeper understanding of the complexities of e-government policy implementation in Indonesia. It offers key recommendations to address political alignment and technical infrastructure challenges, with broader implications for optimizing e-government policies in developing nations.